„Vectes” i „vestes”. Dwie lekcje antycznego tekstu i dwie różne imitacje - Głombiowska, Zofia (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The article shows the Horatian ode III 26 on the background of the votive epigram and in reference to the custom and at the same time the topos of „winning” by violence the house of a lover (frangere postes) and the way of imitating this ode by Filip Buonaccorsi Kallimach in the XXVII elegy and by Jan Kochanowski in the elegy II 11 (in the version preserved in the so-called Osmólski’s manuscript). Callimachus had the text of the ode with the lesson of vestes in verse 7, Kochanowski with the lesson of vectes. As a consequence, in Kallimach’s elegy there is no topos of breaking the door, but the motif of the victorious militia amoris remains, while Kochanowski uses the topos of frangere postes, but departs with love, Lydia and the goddess Venus not with the satisfaction of a victorious soldier, but similarly to Propertius in anger and with a feeling of experienced harm.